"To Save the Innocent, I Demand the Guilty": The Huddy-Asgill Affair - Duke, Claire A . (Kansas State University. Dept. of History, 2017)
The Huddy-Asgill affair, though a supposedly minor event, illustrated important aspects of the American Revolution. It was emblematic of much larger issues of this period. The affair exemplified the volatile, civil war-like atmosphere between loyalist and patriot populations, and reflected polarized public opinions, both in the colonies and abroad, and their impact on the decisions of American leadership.
Keywords: Washington; Patriot; Loyalist; Public Opinion; American Revolution; Retaliation